2020
DOI: 10.2967/jnumed.120.254508
|View full text |Cite
|
Sign up to set email alerts
|

Response evaluation and survival prediction following PD-1 immunotherapy in patients with non-small-cell lung cancer: comparison of assessment methods.

Abstract: Immunotherapy using programmed cell death (PD)-1 blockers is a promising therapeutic modality for nonsmall-cell lung cancer (NSCLC). Therefore, defining the most accurate response criteria for immunotherapy monitoring is of great importance in patient management. This study aimed to compare the correlation between survival outcome and response assessment assessed by PET Response Criteria in Solid Tumors (PERCIST) 1.0, immunotherapy-modified PERCIST (imPERCIST), Response Evaluation Criteria in Solid Tumors (REC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…Actually, not. Some reports have attempted to compare various methods, particularly in melanoma and NSCLC patients [ 14 , 38 , 39 , 40 , 41 , 42 , 43 ], proving the superiority of some of the utilized criteria over others ( Table 2 ). Ultimately, all available response criteria, metabolic or morphological, retain the capability to predict response and outcome.…”
Section: Response Assessment In Solid Tumors Treated With Checkpoint Inhibitorsmentioning
confidence: 99%
“…Actually, not. Some reports have attempted to compare various methods, particularly in melanoma and NSCLC patients [ 14 , 38 , 39 , 40 , 41 , 42 , 43 ], proving the superiority of some of the utilized criteria over others ( Table 2 ). Ultimately, all available response criteria, metabolic or morphological, retain the capability to predict response and outcome.…”
Section: Response Assessment In Solid Tumors Treated With Checkpoint Inhibitorsmentioning
confidence: 99%
“…In addition, response assessment on CT and 18 F-FDG PET was performed according to morphological criteria such as the RECIST and metabolic criteria such as the immunotherapy-modified PET Response Criteria in Solid Tumors (imPERCIST). 15 The authors concluded that 18 F-FDG PET according to the imPERCIST criteria after 3 or 4 cycles of ICIs correctly identified therapeutic response and predicted survival compared with CT according to the RECIST. The level of 18 F-FDG accumulation within tumor cells was able to discriminate between patients with longer and shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“… 28 As dual-time-point evaluation scale, imPERCIST introduces a need to confirm a PD such as the updated radiological criteria, but such a control may limit the risk of a false-positive PET scan. 29 The DR case presented in Figure 1 was classified as metabolic PD by PERCIST because of the appearance of a new metabolic lesion in the proximal right humerus but a partial metabolic response by imPERCIST. Thus, DR should not simply be included in the category of progressive, stable, or responsive disease.…”
Section: Definition Of Immune-related Dr By Radiological Evaluation C...mentioning
confidence: 99%